Efficient Software Development Process Using Component-Based and ORM - Kharisma Rizki Hidayatullah; Hadiq Hadiq (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
The software development process has many variations. Each software development technique has its own advantages and disadvantages. There are efficient development processes and some could be more efficient. This research aims to build a web-based application efficiently utilizing component-based and ORM with a case study of financial management applications on community radio. This research begins with data collection through observations and interviews, requirement analysis, and system design, implementation, and testing. This research shows that combining component-based software development and object-relational mapping (ORM) can increase software development efficiency compared to non-component-based and pure SQL.